Analisis Kadar Ion Pb2+ Pada Kangkung Darat (Ipomea Reptans Poir) Yang Diberi Air Lindi Dari Tpa Sampah Bukit Pinang Samarinda - Hamsina Hamsina; Bohari Yusuf; Erwin Erwin (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2017)
The Research to determine the levels of Pb ion on swamp cabbage (Ipomoea reptans Poir) where each of media cropping given variation of leachate volume from TPA Bukit Pinang Samarinda for every 10 kg of soil has been carried out. Swamp cabbage was analyzed in the roots, stems and leaves at the age of 2 weeks to 4 weeks. The levels of Pb2+ ion was determined by dry destruction method, then measured by atomic absorption spectrophotometry. Pb2+ ion was accumulated on the ground kale plants. The highest levels of Pb2+ ion was contained in the roots of ground kale plants on media cropping which added 1.5 L of leachate at the age of 3 weeks of 2.0642 mg / kg wet weight. The lowest level of Pb2+ ion was contained in the leaves of control plants at the age of 2 weeks that was 0.0177 mg / kg wet weight.